Caracterização do Canal Central da Baía da Ilha Grande com Base em Sísmica Rasa de 7,0 kHz. - Silva, Cristiano Fontoura da (2001)
This work was developed in the central region of the Ilha Grande Bay and was aimed to characterize the sedimentary evolution of the study region using sub-bottom profiler (7,0 kHz) and core data. The data was collected by two surveys, one of them using sub-bottom profiler and the other using core sampler. The shallow seismic profiles were interpreted in order to identify the echocharacters due to textural variations. The core data were processed and samples were collected for granulometric analysis together with, water contents and carbonate contents. In one of the cores, it was also done Pb210 dating. Although seven different kinds of echoes had been identified, it was not possible to justify them when comparing with the core data. This distortion in the seismic profiles could be due to the non-use of TVG. The data shows that the basement is deeper in the narrowest part of the central channel of the Ilha Grande Bay, when compared with the outermost parts of the seismic profiles. The seismic profiles show indications of fault plains, which could be related to the formation of the central channel of the Ilha Grande Bay. In this same region it was also found typical erosional feature, indicating that this region might be subject to sporadic currents. These currents seem to be intense enough to avoid significative sedimentation, in this area unlike other areas around Ilha Grande Bay. The Pb210 dating revealed a sedimentation rate of 6mm/year outermost from the narrow central channel. These results are similar to others research works in the Ilha Grande Bay. Because of the trapped sedimentary units founded, it can be suggested that the sedimentation is major related to the structural pattern and minor to sedimentary supply and hydrodynamics.